Trans-Vessel Wall Cell Transplantation, Engraftment, and Tumor Access in the VX2 Rabbit Model - Victoria Lövljung; Mathias Waldén; Mikael Sandell; Peter Damberg; Staffan Holmin; Fabian Arnberg Sandor (Cell Transplantation)
The trans-vessel wall device (TW-device) is a new endovascular tool for precise and safe delivery of various payloads (cells, viral, modified RNA, chemotherapy, growth factors) in oncology and regenerative medicine. The twofold aim of this study was to assess cell engraftment and tumor growth using the TW-device for endovascular transplantation and to evaluate its ability to directly access solid tumors. We used the VX2 model in the rabbit kidney to compare percutaneously implanted fresh VX2 cells with TW-device injections of cryopreserved VX2 cells. We demonstrated the feasibility of endovascular transplantation ( n = 7) of tumor cells, achieving a 57.1% engraftment rate despite cryopreservation, comparable with 70% for percutaneous delivery of fresh cells ( n = 10). Re-access using the TW-device was 100% successful ( n = 11) with super-selective intratumoral contrast administration without complications. In conclusion, endovascular transplantation of VX2 cells using the TW-device resulted in proliferating cell grafts in the rabbit kidney establishing functional proof that cells indeed survive handling, preparation, and device passage. We also show the TW-device is able to access solid tumor parenchyma allowing precise intraparenchymal administration.This proof-of-concept study open up possibilities for repeated direct parenchymal injections via the endovascular route in any hard to reach organ.